2019
DOI: 10.48550/arxiv.1902.07214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalar Democracy

Christopher T. Hill,
Pedro A. N. Machado,
Anders E. Thomsen
et al.

Abstract: We conjecture that there exists a scalar bound state for every pair of fundamental fermions at a UV ("composite") scale, Λ v weak . This implies a large number of universally coupled, sub-critical Higgs doublets. All but the Standard Model Higgs are "dormant," with large positive squared masses and each receives a small vacuum expectation values via mixing with the Standard Model Higgs. Universal couplings, modulo renormalization group running effects, flips the flavor problem into the masses and mixings of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…We will focus, for simplicity, upon the third generation, and will ignore masses and mixings involving the lighter two generations. We note that, in a previous study, [2], the flavor constraints on this system were found to be consistent.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations

Where are the Next Higgs Bosons?

Hill,
Machado,
Thomsen
et al. 2019
Preprint
Self Cite
“…We will focus, for simplicity, upon the third generation, and will ignore masses and mixings involving the lighter two generations. We note that, in a previous study, [2], the flavor constraints on this system were found to be consistent.…”
Section: Introductionsupporting
confidence: 77%
“…In a larger framework with a UV completion, such as Ref. [2], at a mass scale, m > M b , both g t (m) and g b (m) will have a common renormalization group equation modulo U(1) Y effects. We implicitly assume that, at some very high scale Λ v, the SU(2…”
Section: The Top-bottom Sub-systemmentioning
confidence: 99%
See 3 more Smart Citations

Where are the Next Higgs Bosons?

Hill,
Machado,
Thomsen
et al. 2019
Preprint
Self Cite